The treasures of Tutankhamun an introduction to ancient Egypt - Hoving, Thomas (Mount Kisko, N.Y. Center for Humanities, 1986)
A portrait of ancient Egyptian civilization as depicted in representative art objects.
Keywords: Tutankhamun -- King of Egypt -- Tomb; Art objects -- Egypt; Egypt -- Civilization -- To 332 B.C.; Egypt -- Antiquities; History; Anthropology; Art studies